ANALISIS DAMPAK IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MISKIN DI KELURAHAN KLAWASIH, DISTRIK SORONG BARAT) - Yudit Yustince Buratehi; Meyta Longkotoy; Agnes Eyne Banea (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study is to analyze how the implementation of the Family Hope Program (PKH) in improving the welfare of the poor in Klawasih Village, West Sorong District, analyzes the impact of the implementation of the Family Hope Program (PKH) in improving the welfare of the poor in Klawasih Village, West Sorong District, and knowing the effectiveness of the Family Hope Program (PKH) in improving the welfare of the poor in Klawasih Village, West Sorong District. The data analysis techniques used are data reduction, data presentation, conclusion drawing, and SWOT analysis. The results showed that 1) The Family Hope Program in Klawasih Village, West Sorong District, started in 2013 until now which aims to reduce poverty has not been implemented effectively. The ineffectiveness of this program is because it is still found to be less targeted and uneven in determining PKH participants, then the ineffectiveness of the timing of disbursement of funds where the time for disbursement of funds is often late and not on time, and the amount of aid funds received by PKH participants does not match the amount required. has been determined by the government which makes this program not in accordance with the objectives, so it has not been able to reduce poverty in Klawasih Village, West Sorong District, 2) The impact felt by PKH recipients is also not optimal, seen from their economic condition which is still lacking , then PKH is considered less effective in improving the welfare of the community in Klawasih Village, West Sorong District, and 3) The Family Hope Program (PKH) in improving the welfare of the poor in Klawasih Village, West Sorong District has not been effective.